2000
DOI: 10.1016/s0029-7844(00)00972-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and reduced risk of ovarian cancer

Abstract: Leisure-time physical activity is associated with reduced occurrence of epithelial ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 41 publications
1
27
2
Order By: Relevance
“…Most case-control studies evaluating physical activity and EOC risk reported inverse associations [17,30,33,34]. Other studies indicate an increased risk of EOC among women with high levels of physical activity compared with women who are less active [31,32], and this was also seen in two prospective investigations assessing EOC risk in relation to physical activity level [4,11].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Most case-control studies evaluating physical activity and EOC risk reported inverse associations [17,30,33,34]. Other studies indicate an increased risk of EOC among women with high levels of physical activity compared with women who are less active [31,32], and this was also seen in two prospective investigations assessing EOC risk in relation to physical activity level [4,11].…”
Section: Discussionmentioning
confidence: 89%
“…Additional hypotheses focus on altered estrogen, androgen, and progestin levels [43], and on ovarian inflammation [33,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous studies have examined if there are particular exposure periods during which physical activity levels influence the risk of ovarian cancer. These have not found differential effects of physical activity on ovarian cancer risk over time, with some studies showing a protective effect [50][51][52][53][54] or null effect [33,55,56] over all time and age periods.…”
Section: Discussionmentioning
confidence: 98%